2017
DOI: 10.1021/acs.jafc.7b00916
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lanthanides in the Traceability of the Milk Production Chain

Abstract: The traceability and authentication of milk were studied using trace and ultratrace elements as chemical markers. Among these variables, the group of lanthanides resulted in being particularly useful for this purpose as a result of their homogeneous distribution inside milk, which showed on the contrary to be intrinsically inhomogeneous from the elemental point of view. Using in this pilot study milk samples from a factory in Piedmont (Italy), we demonstrated that the distribution of lanthanides can be used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
2
14
0
2
Order By: Relevance
“…Usually all rare earths in different materials follow the same pattern, i.e., they are all enriched or depleted: fava Santorini’s [26]; Italian milk [30]; mushrooms substrates [31]. However, this pattern is differentiated by genetic factors as seen in two different mushroom species [31].…”
Section: Resultsmentioning
confidence: 99%
“…Usually all rare earths in different materials follow the same pattern, i.e., they are all enriched or depleted: fava Santorini’s [26]; Italian milk [30]; mushrooms substrates [31]. However, this pattern is differentiated by genetic factors as seen in two different mushroom species [31].…”
Section: Resultsmentioning
confidence: 99%
“…A particular focus must be given on the discrimination power of lanthanides. It is well known their role in providing a link between a specific territory and foodstuffs that originate from it, as a consequence of their homogeneous chemical behaviour, which is not fractionated in the passage between soil, plant and food final product [11][12][13]. As far as wine is concerned, our previous work [14] and other works suggested that its production chain can cause fractionation of the original soil fingerprint.…”
Section: Barbera 100%mentioning
confidence: 89%
“…Lanthanides are widely exploited in food authentication and traceability studies (Ballabio et al 2018;Manfredi et al 2018;Aceto et al 2013;Marengo et al 2005;Aceto 2016;Aceto et al 2009Aceto et al , 2017Aceto et al , 2019Oddone et al 2009). The first ones are devoted to distinguish food differences related to the geographical provenance, the botanical or animal variety, the technological process of production or the coherence to the disciplinary of production.…”
Section: Lanthanides In Foodstuffs Traceability and Authenticationmentioning
confidence: 99%
“…A recent study (Aceto et al 2017) involved milk, characterized by a quite long production chain, since traceability should be guaranteed from the soil on which the animal feed is cultivated to the final product. Proving the traceability in these conditions is quite challenging due to the animal metabolism that could alter the REEs profile.…”
Section: Milkmentioning
confidence: 99%